Mergers and shareholder wealth in European banking - Cybo-Ottone, Alberto; Murgia, Maurizio (Journal of Banking & Finance, 2000)
We study the stock market valuation of mergers and acquisitions in the European banking industry. Based on a sample of very large deals observed from 1988 to 1997 we document that, on average, at the announcement time the size-adjusted combined performance of both the bidder and the target is statistically significant and economically relevant. Although our sample shows a great deal of cross-sectional variation, the general results are mainly driven by the significant positive abnormal returns associated with the announcement of domestic bank to bank deals and by product diversification of banks into insurance. On the contrary, we found that M&A with securities firms and concluded with foreign institutions did not gain a positive market's expectation. Our results are remarkably different from those reported for US bank mergers. We explain our different results as stemming from the different structure and regulation of EU banking markets, which are shown to be more similar between them than as compared with the US one.